Therapeutics in veterinary care of the donkey. (2nd January 2023) - Sullivan, Rebekah; Vogel, Polly
Abstract : Knowledge of donkey-specific disease presentation, behaviour, anatomy and physiology is beneficial when choosing appropriate medications and routes of administration in this species. While many selected therapeutic agents will be the same as those used in the horse, being aware of certain nuances will ensure that the donkey receives the best possible care. Clinicians and owners alike may benefit from drug administration tips. As there are limited drugs licensed for use in the donkey, use of the prescribing cascade is usually warranted. This article mentions the use of therapeutics in mules where appropriate.